HİSSE SENETLERİ İÇİN VERASET VERGİSİNDE İKMAL TARHİYATI, CEZA VE GECİKME FAİZİ - (:unkn) unknown (My University, 2017)
Sermaye Şirketi hisselerinin veraset vergisine konu olması halinde vergilendirme yöntemi, Kanunun iki dereceli tarh usulünü öngördüğü, yapılacak ikinci ve son tarhiyatın ikmal tarhiyatı niteliğinde olduğu, bunun ise ikmalen tarhiyattan farklı ve kendine özgü bir vergilendirme yöntemi olduğu, bu nedenle söz konusu ikinci vergilendirmede ceza ve gecikme faizinin uygulanamayacağı, işbu makaleye konu edilmiştir.

When stock certificates are the subject matter of estate tax, the taxation method that is prescribed under the law is a two tiered assesment; the second, and the last assesment to be conducted has the attributes of an additional assesment, which is different, and distinct from additional assesment. Therefore, punitive, and default interests may not be implemented on the second taxation. This is the subject matter of the following article.
CONSUMMATION ASSESMENT, PUNITIVE, AND DEFAULT INTEREST OF ESTATE TAX FOR STOCK CERTIFICATES
Keywords: Hukuk